Radiation-induced optic neuropathy after stereotactic and image guided intensity-modulated radiation therapy (IMRT). (May 2019) - Brecht, Susan; Boda-Heggemann, Judit; Budjan, Johannes; Siebenlist, Kerstin; Stieler, Florian; Steil, Volker; Wenz, Frederik; Lohr, Frank; Buergy, Daniel
Highlights: Severe RION is rare after normofractionated stereotactic IGRT/IMRT (incidence 1.2%) The RION risk did not increase at doses of ≤55 Gy, 55–58 Gy or 13 patients with ≥58 Gy. The risk of tumor-associated blindness or death was higher in all dose strata. In aggressive tumors, point doses of 58 Gy to the optical pathway may be acceptable. Abstract: Background/purpose: To quantify the risk of radiation-induced optic neuropathy (RION) after stereotactic/image-guided positioning and intensity-modulated radiotherapy (IMRT) with ≥50 Gy to the anterior visual pathway (AVP). Methods: Patients irradiated with ≥50 Gy to the AVP using stereotactic/image-guided positioning between 2002 and 2011 in Mannheim were identified. Detailed dosimetric data were collected and patients or family members were retrospectively asked to rate visual acuity and visual disorders. Results: 125 patients fulfilled the eligibility criteria. Average maximum equivalent point dose (Dmax -EQD-2[α/β=1.6] ) to the AVP was 53.1 ± 3.9 Gy. 99 patients received ≥50 Gy bilaterally (chiasm or both optic nerves), resulting in 224 (99x2 bilateral plus 26 unilateral) visual-fields-at-risk (VFAR) for RION. Eighty-two patients provided pre/post-IMRT visual status information ( n = 151 VFARs). Permanent visual deterioration occurred in 18 (22%) patients. In seven, visual deterioration was possibly related to radiotherapy (two-sided deterioration in one patient) for a crude incidence of 8.5% (7/82 patients) and 5.3% (8/151 VFARs). Two cases were caused by chronic keratitis/conjunctivitis; in five patients RION could not be excluded (one two-sided). In one of 13 patients with Dmax -EQD-2 > 58 Gy, RION could not be excluded. In all affected patients, visual acuity post-IMRT had decreased only mildly (1–2 points on the 5-point-scale). One patient with relevant baseline visual impairment (3/5) developed unilateral blindness (crude incidence of blindness on patient-/VFAR-level: 1.2% and 0.66%; competing risk-adjusted/actuarial 24-month incidence: patient/VFAR-level: 1.8% and 0.95%). Conclusion: Risk of RION was low in this cohort with accurate positioning and precise dosimetric information. Less conservative tolerance doses may be considered in patients with high risk of recurrence.